Chromium histidinate protects against heat stress by modulating the expression of hepatic nuclear transcription factors in quail - Orhan, C.; Akdemir, F.; Şahin, Nurhan.; Tuzcu, M.; Komorowski, J. R.; Hayirli, A.; Şahin, Kazım (Taylor & Francis Ltd, 2012)
1. This experiment was conducted to evaluate the effects of supplemental chromium histidinate (CrHis) on performance and expressions of hepatic nuclear factors kappaB, an enhancer (NF-B) and an inhibitor (IB) of activated B cells in heat-stressed Japanese quail (Coturnix coturnix japonica). 2. A total of 180, 10-d-old Japanese quail were allocated randomly into 6 groups in a 2x3 factorial arrangement. Birds were reared either at 22 degrees C for 24h/d (thermoneutral, TN) or 34 degrees C for 8h/d (heat stress, HS) for 32d and fed on one of three diets supplemented with 0, 400 or 800 mu g of CrHis per kg of diet. Each group consisted of 10 cages, each containing three quail. Data (performance variables and hepatic NF-B and IB) were analysed using 2-way ANOVA. 3. Heat stress caused reductions in cumulative feed intake (FI) by 5 center dot 7%, weight gain (WG) by 13 center dot 0%, final body weight (FBW) by 10 center dot 3%, carcase weight by 12 center dot 6% and carcase efficiency by 2 center dot 3% and an increase in feed conversion ratio (FCR, feed consumed, g:weight gained, g) by 8 center dot 4%. As supplemental CrHis level increased up to 800 mu g/kg, there were linear increases in cumulative FI (from 602 to 609g), WG (from 134 to 138g), FBW (from 167 to 171g), cold carcase weight (from 110 to 114g) and cold carcase efficiency (from 65 center dot 5 to 66 center dot 4%) and a decrease in FE (from 4 center dot 51 to 4 center dot 42). The environmental temperature by CrHis level interaction effect on performance parameters was insignificant. Hepatic NF-B p65 concentration was higher and hepatic IB concentration was lower in quail exposed to HS than in quail kept at TN temperature. Increasing supplemental CrHis level linearly inhibited hepatic NF-B p65 expression from 134 center dot 4 to 105 center dot 3% and linearly enhanced hepatic IB expression from 73 center dot 4 to 99 center dot 6%. The decrease in hepatic NF-B expression and the increase in hepatic IB expression were more notable in the TN environment than in the HS environment. 4. In conclusion, heat stress depressed performance variables and augmented lipid peroxidation and supplemental CrHis alleviated oxidative stress through modulating expressions of stress-related hepatic nuclear transcription factors (NF-B and IB).
Keywords: Factor-Kappa-B; High-Fat Diet; Lipid-Peroxidation; Insulin-Resistance; Serum Metabolites; Egg-Production; Picolinate Supplementation; Oxidative Stress; Skeletal-Muscle; Tnf-Alpha